The Calculation of Erosion and Sedimentation Rate in Coastal Zone Using Satellite Imageries (Case Study: Kecamatan Muara Gembong, Kabupaten Bekasi, West Java) - Dianlisa Ekaputri; Wiwin Windupranata; Agung Budi Harto (Indonesian Journal of Geospatial, 2014)
Abstract. Coastal zone is a transition area which always influenced by the changes of the land and ocean. The changes may occur due to the tide, current, wave, wind, sea water intrusion, runoff, contamination, or continental shelf area. As an effect, erosion and sedimentation phenomenon are occurred and could cause the changes of coastline shape. Kecamatan Muara Gembong which belongs to Kabupaten Bekasi is located in the Northern Coast of Java Island. Due to its geographical location, this area is threatened by the risk that is caused by erosion and sedimentation in the coastal zone. Therefore, study in this area is needed in order to identify the changes of the coastline. Coastline mapping through spatio-temporal LANDSAT-7 ETM+ satellite imageries is one of the methods to conduct this study. It uses satellite images from year 2000